The Best of Both Worlds: Staged Hybrid Approach to Complex Cardiac Disease in a Patient at High Surgical Risk - Conradi, Lenard; Baldus, Stephan; Treede, Hendrik; Seiffert, Moritz; Schirmer, Johannes; Rudolph, Volker; Blankenberg, Stefan; Reichenspurner, Hermann (The Thoracic and Cardiovascular Surgeon, 2013)
For elderly patients with relevant comorbidities, combined cardiac surgery may be inadequate due to excessive surgical risk. Combining interventional valvular and surgical approaches may decrease surgical burden and operative risk. In the present case, we report a staged strategy of interventional mitral valve repair and secondary surgical aortic valve replacement and replacement of the ascending aorta in a patient at high risk for surgery. This hybrid approach allowed for substitution of one part of surgery by the relatively low-risk MitraClip procedure. For the future, increasing clinical importance of interventional valve therapies either for stand-alone or hybrid procedures can be anticipated.
Keywords: aortic valve; replacement; mitral valve repair